1979
DOI: 10.2466/pr0.1979.44.3.880
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian and Traditional Mothers' Responses to Adult Response to Child Behavior and Self-Concept

Abstract: A purposive sample of 34 lesbian and 47 traditional mothers was located in the Denver-Fort Collins area. This pilot study was designed to determine if statistically significant differences existed between the two groups of mothers on measures of maternal attitude and self-concept. The Adult Response to Child Behavior, a set of slides of children's behaviors and set responses, provided an indicator of adult-, task-, and child-centered attitudes. Three personality aggregates, self-confidence, dominance, and nurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 5 publications
0
39
0
1
Order By: Relevance
“…A number of studies have compared the overall mental health of lesbian mothers with that of heterosexual mothers. The results show that there are no differences in psychological health between lesbian mothers and divorced heterosexual mothers in self-concept (Mucklow & Phelan, 1979;Rand, Graham, et al, 1982), happiness (Rand, Graham, & Rawlings, 1982) and overall adjustment and psychiatric status (Golombok, Spencer, & Rutter, 1983 ). Furthermore, Rand et al (1982) Miller, Jacobsen and Bigner (1981) investigated 34 lesbian and 47 heterosexual mothers, and reported that the former group was more child oriented in disciplinary techniques than the latter group was.…”
Section: Parental Functioningmentioning
confidence: 85%
See 1 more Smart Citation
“…A number of studies have compared the overall mental health of lesbian mothers with that of heterosexual mothers. The results show that there are no differences in psychological health between lesbian mothers and divorced heterosexual mothers in self-concept (Mucklow & Phelan, 1979;Rand, Graham, et al, 1982), happiness (Rand, Graham, & Rawlings, 1982) and overall adjustment and psychiatric status (Golombok, Spencer, & Rutter, 1983 ). Furthermore, Rand et al (1982) Miller, Jacobsen and Bigner (1981) investigated 34 lesbian and 47 heterosexual mothers, and reported that the former group was more child oriented in disciplinary techniques than the latter group was.…”
Section: Parental Functioningmentioning
confidence: 85%
“…Cognitive functioning. Two studies (Kirkpatrick, Smith, & Roy, 1981;Green, Green, 1978Mucklow & Phelan, 1979Lewis, 1980Hoeffer, 1981Kirkpatrick, 1981Miller, Jacobsen, & Bigner, 1981 Children …”
Section: Child Developmentmentioning
confidence: 99%
“…The former paper found numerous diff erences in educational outcomes, with substantial eff ect sizes (as large as 3.75) between outcomes for children of same-sex vs. heterosexual parents ( Schumm, 2015c ), while the latter dissertation reported signifi cantly and substantially lower family togetherness in drawings by children of same-sex parents relative to children of heterosexual parents. Furthermore, Patterson (2005 ) cited two studies ( Mucklow & Phelan, 1979 ;Miller, et al, 1981 ) by the same authors using the same data that featured results favorable to lesbian families but omitted in her bibliography one study from the same authors ( Miller, et al, 1980 ) that had featured adverse results for lesbian families. Patterson (2005 ) also did not cite any of the additional research done by Sarantakos (1996bSarantakos ( , 1998Sarantakos ( , 2000 on same-sex families, as described in more detail elsewhere ( Schumm, 2015c ).…”
Section: Ideology May Be Accepted Over Scientifi C Evidencementioning
confidence: 99%
“…For example, I found two journal articles ( Mucklow & Phelan, 1979 ;Miller, et al ., 1980 ), both published in the same journal by the same group of scholars at about the same time and using the same sample. The study of lower methodological quality ( Mucklow & Phelan, 1979 , cited 72 times according to Google Scholar as of December 18, 2015) has been cited far more often than the other ( Miller, et al ., 1980 , cited 9 times as of December 18, 2015). The only real diff erence in this natural experiment appears to have been that one study presented (currently) politically correct results, while the other did not ( Schumm, 2010d ).…”
Section: High (Or Low) Quality = Cited Often (Or Infrequently)mentioning
confidence: 99%
“…(How would a scholar know the empirical answer to that question?). If you, as a conservative, publish an article in a lower tier journal, you may be criticized by lawyers as if your research is useless, even though there is evidence that journal tiers and citation rates do not always correspond [5] [79]; yet, if an article [25] published in a lower tier journal supports a liberal objective, seldom will you hear those scholars or their research criticized by lawyers on that basis. I have had a legal association challenge my right as a journal editor to publish controversial comments or research articles.…”
Section: Rejection By Lawyersmentioning
confidence: 99%